COMPREHENSIVE OBJECTIVE CARE IN NY “W” G1P0A0 WITH SWOLLEN LEGS AND BLISTERING NIPPLES IN CLINIC "BI" CIPATAT DISTRICT WEST BANDUNG - Faizah, Siti; Mariyati, Sri; Sarikah, Iik (Lux Mensana: Journal of Scientific Health, 2023)
Introduction to this study Physiological changes in pregnant women are changes in shape or anatomical and hormonal changes. Swelling of the legs is one of the pregnancy discomforts that pregnant women often complain about. According to the results of a survey at the "BI" CLINIC of 61 pregnant women encountered, as many as 49 experienced the discomfort of swelling of the legs and there were 10 puerperal mothers and 2 of them had nipple blister problems. The purpose of this study was to be able to provide comprehensive obstetric care to Mrs. "W" by giving warm water baths, at the "BI" Citatah Clinic, Cipatat District. Methods The research method used is a case study study by conducting an assessment and upbringing the subject of the study, namely Mrs. "W" with complaints of leg swelling in the III trimester pregnancy. Results & Analysis. The results of the case study carried out were the provision of soaking soaking warm water with a temperature of 380C for 20 minutes carried out 3 times a day regularly, so that the mother felt that the swelling that the mother experienced was reduced. In the puerperium, the mother experiences blistered nipples and is given breastfeeding technique care and the results of the nipples heal after 6 days. Discussion. The conclusion of this case study is that after a warm water bath for 2 weeks with 3x sahari the natural swelling is reduced, as well as in the puerperium the lecat nipples heal after being given the correct breastfeeding technique care.